CURRENT STATE OF FORMATION OF LOCAL BUDGET REVENUES - Umarov O’tkir (Academia Science Repository, 2023)
State budget _ _ national finance system e throne the neck as state by k e ng scale social reforms done increase financial source being service to do with together , the country in the economy done being increased reforms state by of support important financial source is considered Especially fundamental component of our economy changes _ done increase , mod e rnization and div e rsification processes consistent continue carry on with dependent k e ng scale reforms done increase such as of duties day order as a matter of urgency to the field release own in turn state of finance central joint calculated state budget _ _ income and expenses efficient manage system to form requirement does _ Because the state budget _ _ income formation in the system priority importance occupation doer taxes by means of of the economy some networks encourage opportunities have if divided , secondly , davla budget _ _ expenses system through strong social politics done increase financial the basics formation with together , centralized funds financial r e sources at the expense of big and strat e gik important have the inv e stition that was projects state at the expense of financing opportunities have is dividing .